Relationship between Apparent Diffusion Coefficients and MR Spectroscopy Findings in High‐Grade Gliomas. Issue 1 (15th April 2016) - Gadda, Davide; Mazzoni, Lorenzo Nicola; Pasquini, Luca; Busoni, Simone; Simonelli, Paolo; Giordano, Gian Paolo
ABSTRACT: BACKGROUND AND PURPOSE: The role of apparent diffusion coefficient (ADC) for preoperative grading and treatment planning of high‐grade gliomas (HGG) is still debated since the assumption of inverse correlation between ADC and cellularity is not completely coherent with the results of some studies. It has been recently hypothesized that restricted diffusivity in HGG may be related to hypoxic/ischemic changes inside the tumor. We therefore investigated the differences of ADC values between areas with magnetic resonance spectroscopy (MRS) markers of hypoxia and necrosis (lactate and lipid compounds) and regions with lack of both metabolites. METHODS: The MRS datasets and the corresponding ADC maps of 28 patients with HGG were retrospectively reviewed. Circular regions of interest (ROIs) were placed on ADC maps by means of spectral characteristics, considering the solid portions of gliomas. One‐way ANOVA or Welch test were performed for multiple comparison of the Mean ADC, minimum ADC (minADC), and standard deviation of pixel‐by‐pixel ADC measurements (ADC SD) values among the groups of ROIs with lactate, lipids, and lack of both metabolites (LAC, LIP, and NEG group, respectively). RESULTS: The minADC values in LAC group (908 ± 161 × 10 −6 mm 2 s −1 ) were found to be significantly ( P = .03) higher than in NEG group (792 ± 122 × 10 −6 mm 2 s −1 ). We did not find other significant differences by the multiple comparison tests. CONCLUSIONS: HGG areas with MRS markers of hypoxia and necrosis are not associated with restricted diffusivity. To explain the trend to diffusion facilitation in HGG lactate‐expressing regions, we hypothesize a possible hypoxia‐induced volume reduction of glioma cells with extracellular shift of cytoplasmic water.